Single National Curriculum English2020Implementation Determinants: Intended and Enacted CurriculumPerspective at Primary Level in Punjab (Journal of Asian Development Studies, 2024)
The current study was designed to determine the gap between the intended curriculum and enacted SNC English 2020 implementation determinants: instructional materials, teaching methods, formative assessment techniques, and professional development. The study was quantitative and descriptive based on the survey method. A self-developed questionnaire was used to collect the data from the teachers in Punjab. Five English curriculum experts ensured the content validity of questionnaires, and reliability was calculated employing Cronbach’s Alpha score of .926. A simple random sampling technique was used to collect from a sample of 268 teachers. The collected data were analyzed employing descriptive and inferential statistics. The result of the study revealed that overall, 62% of the curriculum was implemented, and a 38% gap existed. The results declared that 54% of instructional materials were in use and a 46% gap existed. The results affirmed that 59% of teaching methods were in use and 41% of the gap existed. The results showed that 62% of teachers were trained, and a 38% gap existed. The results asserted that 71% of formative assessment strategies were in use, and a 29% gap existed.Furthermore, results delineated a significant difference in locale regarding teaching methods and teachers’ professional development. Based on the study results, it was recommended that the government should provide funds for English instructional materials and English curriculum-based teacher training on using instructional materials, teaching methods, and assessment. The education department and head teachers may bind teachers to use English curriculum-based implementation guidelines.